My life, my Home: Reasserting the connection between home and occupant - Barends, Franko (Faculty of Engineering and the Built Environment, 2023)
The intent of this paper is to uncover an architectural typology for a people who have none. An architectural typology that speaks to a culture and life of the people that live at the margins. I uncovered and have experienced that there is a lack of architectural representation of the people that live at the margins. I have taken on this responsibility to uncover an appropriate typology for these people. The reason for this lack of representation is that the people at the margins endured a plethora of cultural influences some their own some not. It is for this reason hybridity is required for this representation. To further enrich the outcome of this study, this paper will be examining the housing typology in various incarnations in different locals and times in history. Looking at different incarnations of the housing typology I would like to understand the role architecture plays in the facilitation of social interaction and the aid it brings to societal ills. I am particularly interested in the housing typology because housing in my view is the singular typology people encounter every day. Housing and the community it implies has the biggest impact on the human experience.